A Theoretical Investigation of Chemical Bonding of a Heterometallic Trinuclear Cluster Containing Iridium and Ruthenium: [(Cp*Ir) (CpRu)2 (μ3-H) (μ-H)3] by QTAIM Approach (Baghdad Science Journal, 2024)
Numerous integral and local electron density’s topological parameters of significant metal-metal and metal-ligand bonding interactions in a trinuclear tetrahydrido cluster [(Cp* Ir) (Cp Ru)2 (μ3-H) (μ-H)3]1 (Cp = η5 -C5Me5), (Cp* = η5 -C5Me4Et) were calculated and interpreted by using the quantum theory of atoms in molecules (QTAIM). The properties of bond critical points such as the delocalization indices δ (A, B), the electron density ρ(r), the local kinetic energy density G(r), the Laplacian of the electron density ∇2ρ(r), the local energy density H(r), the local potential energy density V(r) and ellipticity ε(r) are compared with data from earlier organometallic system studies. A comparison of the topological processes of different atom-atom interactions has become possible thanks to these results. In the core of the heterometallic tetrahydrido cluster, the Ru2IrH4 part, the calculations showed that there are no bond critical points (BCPs) or identical bond paths (BPs) between Ru-Ru and Ru-Ir. The distribution of electron densities is determined by the position of bridging hydride atoms coordinated to Ru-Ru and Ru-Ir, which significantly affects the bonds between these transition metal atoms. On the other hand, the results confirm that the cluster under study contains a 7c–11e bonding interaction delocalized over M3H4, as shown by the non-negligible delocalization index calculations. The small values for ρ(b) above zero, together with the small values, again above zero, for Laplacian ∇2ρ(b) and the small positive values for total energy density H(b), are shown by the Ru-H and Ir-H bonds in this cluster is typical for open-shell interactions. Also, the topological data for the bond interactions between Ir and Ru metal atoms with the C atoms of the cyclopentadienyl Cp ring ligands are similar. They show properties very identical to open-shell interactions in the QTAIM classification.